Ethics of Using Artificial Intelligence Reviewed from Pancasila and Bhinneka Tunggal Ika - Ardi Tri Yuwono; Andi Sebastian; Pieter-Jan Clumpers; Mustafa Basara (Bhinneka Tunggal Ika: Pancasila Jurnal Internasional Berbahasa Indonesia, 2026)
The global development of Artificial Intelligence (AI) frequently overlooks local values, potentially marginalizing cultural diversity, as observed in the Indonesian context. This research aims to formulate a contextual AI ethical framework rooted in Pancasila and Bhinneka Tunggal Ika. Employing a philosophical-conceptual approach with hermeneutic analysis, this study operationalizes abstract national values into concrete ethical guidelines. The framework comprises five core principles: (1) Transcendental Responsibility; (2) Human-Based Justice; (3) Digital Sovereignty and Social Cohesion; (4) Deliberative Governance; and (5) Distributive Justice. Furthermore, the principle of Bhinneka Tunggal Ika is integrated to ensure inclusivity and prevent technological cultural homogenization. This framework addresses the vacuum in national norms while offering a corrective perspective on cultural biases within universal AI ethics discourse. The findings serve as a strategic guide for AI governance, design, and auditing that is responsive to Indonesia’s pluralistic society and aligned with the Sustainable Development Goals (SDGs).